Modular cognitive‐behavioral therapy for affective symptoms in young individuals at ultra‐high risk of first episode of psychosis: Randomized controlled trial. Issue 3 (19th November 2019) - Pozza, Andrea; Dèttore, Davide
Abstract: Objectives : Individuals at ultra‐high risk of psychosis often present concurrent affective symptoms (depression/anxiety). This study investigated whether modular cognitive‐behavioral therapy (CBT) targeting both ultra‐high risk and affective symptoms (a) reduced/delayed risk of a first psychotic episode at posttreatment and 14‐month follow‐up compared with a supportive intervention, (b) was more effective than control condition in producing remission on depression/anxiety. Methods : Fifty‐eight ultrahigh risk individuals were randomly assigned to CBT or control condition. CBT consisted of 30 sessions, including CBT for psychotic experiences and depression/anxiety. Results : In the CBT group, the cumulative number of participants who developed a first psychotic episode ( n  = 3, 10.34%) at follow‐up was lower than in the control group ( n  = 8, 27.60%; logrank  χ 2 (1)  = 3.68, p  = .05). In the CBT group, a higher number of participants achieved remission than in control condition on affective symptoms at posttreatment/follow‐up. Conclusion : CBT can prevent psychosis risk and produce better outcomes on depression/anxiety than supportive intervention.